2012
DOI: 10.1021/ie202757k
|View full text |Cite
|
Sign up to set email alerts
|

Water-Assisted Solvent Extraction of Bitumen from Oil Sands

Abstract: Water-assisted solvent extraction processes (WASEPs) were developed by introducing a water layer between the oil sands and solvent to extract bitumen from oil sands. The extraction condition was well investigated using the naphtha as the extraction solvent. Considering the extraction cost, the advised extraction processes for industrial application were conducted under stirring at temperature of 50−60 °C for 30 min using a ratio of oil sands to naphtha to water in 1:1:0.5 (wt/wt/wt). At such conditions, bitume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 22 publications
1
33
0
Order By: Relevance
“…Solvent extraction of bitumen as an alternative technology to the current warm water extraction process offers high bitumen recovery (> 90 %) from a range of ores . Several promising solvents have been identified including aromatics, n ‐alkanes, and cycloalkanes .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Solvent extraction of bitumen as an alternative technology to the current warm water extraction process offers high bitumen recovery (> 90 %) from a range of ores . Several promising solvents have been identified including aromatics, n ‐alkanes, and cycloalkanes .…”
Section: Introductionmentioning
confidence: 99%
“…[1] Solvent extraction of bitumen as an alternative technology to the current warm water extraction process offers high bitumen recovery (> 90 %) from a range of ores. [3][4][5][6][7][8][9][10][11][12][13][14][15] Several promising solvents have been identified including aromatics, n-alkanes, and cycloalkanes. [11,12,15] The extraction gangue, a mixture of sands and fine solids after solvent extraction, is almost dry and can be stacked, allowing for fast reclamation of the mining site.…”
Section: Introductionmentioning
confidence: 99%
“…One alternative technology is extraction of bitumen by dissolution in light hydrocarbon solvents instead of flotation in hot water . With recoveries of 80–95 %, this method is less sensitive to variation in the grade of the ore and the surface properties of the solids . Low‐boiling solvents can be recovered by evaporation from the waste stream, or gangue .…”
Section: Introductionmentioning
confidence: 99%
“…[4] With recoveries of 80-95 %, this method is less sensitive to variation in the grade of the ore and the surface properties of the solids. [5][6][7][8][9][10][11][12] Low-boiling solvents can be recovered by evaporation from the waste stream, or gangue. [6][7][8]11,[13][14][15][16][17][18][19][20][21][22][23][24][25] Low losses of solvent in the gangue are essential for an economical process that is environmentally acceptable, [26] and achieving such results on a commercial scale for oil sands is a major technological challenge.…”
Section: Introductionmentioning
confidence: 99%
“…11 The effect of weathering on oil sands processability has been reported recently. 9,[12][13][14][15][16] By studying a laboratory weathered ore and a naturally weathered ore, a mechanism on the deteriorated processability of oil sands due to weathering was proposed by Masliyah and coworkers. 11,13 It was suggested that the formation water loss because of weathering led to a close contact of bitumen with the solids surface and hence resulted in the adsorption of organic matter.…”
Section: Introductionmentioning
confidence: 99%